Point of Sale (POS) Application in Plastic Shops in Bumdes Ngarum Village, Sragen District Based on Website - Utomo, Ihsan Cahyo; Priyawati, Diah; Abas, Novel Idris; Ummah, Khanun Roisatul; Septa Riani, Lencia Putri (Institut Teknologi Bisnis AAS Indonesia, 2024)
Transaction sell buy at the shop plastic in village BUMDES Ngarum happen every day with large amount. In transactions sell buy during This Still carried out manually with _ write on note paper, then new do recap on the book transaction every the day. In doing data collection goods, shops Plastic in BUMDES Ngarum Village during This Still done manually, that is with write goods that come in and goods that go out in a book. System ongoing management _ done manually, create management goods become not enough effective and efficient, so needed something more system _ as effective as it can be accessed with fast and easy that is with develop Point of Sale (POS) application in stores plastic in village BUMDES Ngarum Regency Sragen Website based. Application Point of Sales (POS) cashier created use waterfall method. The waterfall method has 5 stages in construction, that is analysis requirements, design, development (coding), testing, and implementation. Results obtained that is web based Point Of Sales application that can make it easier recording, managing and storing data on goods and transactions carried out. The system also helps minimize possible errors occurs in the calculation transactions and make it easier in search for the desired data.